GAMBARAN PERILAKU MAHASISWI DALAM PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Indriati Andolita Tedju Hinga (CHMK HEALTH JOURNAL, 2019)
One method for early detection of breast cancer is SADARI (check your own breast). SADARI is the cheapest, safest and simplest way because it can be done alone. SADARI is very important to do because almost 85% of breast lumps are found by the patient herself. College Student are included in a group a risk of breast cancer because patients diagnosed with breast cancer are in the age range of 25-69 years. This study aims to find out the description of self-breast examination behavior of the students of public health study program. This type of research is descriptive research with survey methods. The population is all regular students of the second until sixth semester of the Faculty of Public Health many as 561 people and a sample of 82 people with Stratified Random Sampling technique. Data analysis used is univariate analysis. The results of this study indicate that as much as 69.5% of respondents had done SADARI, but only 17.9% did it regularly, most of the respondents had good knowledge (65.8%), all respondents had a positive attitude, and most respondents did not get support from parents (75.6%) and peers (71.9%). Health students should be able to do SADARI regularly with the right procedures and be able to teach, encourage and remind friends, family or others about the importance of early detection of breast cancer. Keywords : Self Breast Examination, Student Behavior.